PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS NEARPOD TEMA ESSEN UND TRINKEN SEBAGAI PELATIHAN KETERAMPILAN MEMBACA XI MAN - Sukmawati, Dewi; Wahyuningsih, Fahmi (LATERNE, 2024)
The development of Nearpod-based learning media was carried out based on problems in learning the German language at MAN 2 Bojonegoro, which were identified through interviews with the school's teachers. The students show less interest in learning, and the class appears less lively. The lack of use of application-based media leads to these problems. The only learning media are books. Based on these issues, this study aims to develop Nearpod learning media on the topic of "Essen und Trinken". Within the framework of this study, Borg and Gall's research and development model was applied. The data were obtained from the results of a media feasibility questionnaire, which was validated by material experts and media experts. The feasibility test results from the material experts were 80%, and the results from the media experts were 84%. From these results, it can be concluded that Nearpod-based learning media are suitable for use as learning media.